Analysis of fixations while solving a test question related to computer networks - Ujbányi, Tibor; Katona, József; Kővári, Attila (Teaching Mathematics and Computer Science, 2018)
Examination of human eye move is useful because by eye tracking and definition of visual attention, may making conclusions about hidden cognitive processes which are harder to examine. With human eye tracking, visual attention can be defined, therefore hidden cognitive processes may be revealed and examined. The goal of the research, presented in this article, to analyze the so called fixation eye movement parameter recorded during a test question related to computer networks. The paper present what significant differences detected between pre-knowledge and the number of fixations using statistical analysis. The results show a moderately relationship between previous knowledge and fixation counts.